Analisis Kepatuhan Petugas Laboratorium dalam Penggunaan Alat Pelindung Diri (APD) di Laboratorium BTKLPP Kelas I Palembang Tahun 2021 - Pradani Yandiono; Akhmad Dwi Priyatno; Dian Eka Anggreny (Jurnal Kesehatan Saelmakers PERDANA, 2022)
Workers safety is one of success indicator in an organization system. This system must be stated in a policy and lowered into standard operating procedures (SOP). Workers safety must be obeyed by all relevant officers involved that job to insure work safety. This study to identify the factors related to compliance of laboratory officers in use Personal Protective Equipment (PPE). This research was used survey method to measure the independent and dependent variables. The analysis used is the chi-square test. This research was conducted on 12 – 26 July 2021 using questionnaire instrument to 23 respondents (laboratory officers) with total sampling technique. This study showed that the average respondent’s was 38 years old. The female respondent was 23 (65.7%), education respondent’s was 18 (41.4%) bachelor degree, working time respondent’s was 32 (91.4%), the availability of facilities was not available 18 (51.4 %), poor supervision 20 (57.1%), good knowledge respondent’s was 33 (94.3%), negative attitude was 19 (54.3%) and compliance 19 (54.3%). The conclusion of this research is that there is a relationship between the variables of gender, supervision of laboratory officer compliance in using PPE and there is not relationship between the education, working time respondent’s. knowledge, attitudes, availability of facilities and age on the laboratory officer compliance in use PPE at BTKLPP Class I Laboratory. Suggestions for BTKLPP class I to carry out socialization and education on product operational standards using PPE, to complete the facilities and availability of personal safety equipment and supervision in use PPE to ensure occupational health and safety.